METODE PEMBINAAN AKHLAK DALAM PENINGKATAN PENGAMALAN IBADAH PESERTA DIDIK DI SMP N 4 SEKAMPUNG LAMPUNG TIMUR - Bayu Prafitri (IAIN Padangsidimpuan, 2018)
Islamic religious education teachers are people who provide knowledge with the aim of educating and fostering the morality of students as good people. In the process of moral development of students, an Islamic education teacher in delivering material must have the right method. Moral material is one of the most dominating material in the formation of personality of students. If the provision of this material is maximally endeavored by the religious teacher, the morality of the participants should be ascertained to be better. In this case the Islamic religious education teacher plays the first and foremost role in the process of moral development of his students. For the success of the moral development process, an Islamic religious education teacher must be able to use several methods in building it to improve the worship experience.Departing from that background, the author wants to discuss it in a thesis and takes the title